MERANCANG KEGIATAN PEMBELAJARAN SEJARAH MELALUI KOMIK: RESPON TERHADAP TANTANGAN KURIKULUM 2013 - Aisiah Anwar (Diakronika, 2017)
Crucial issues, as well as the classic issues that have always been the subject of historical learning problems related to activities or learning processes that tend to be monotonous, boring and lack of innovation and creativity of the teachers in designing historical learning activities that can generate students interest and motivation in learning the history. The 2013 curriculum presents a special challenge for teachers to design studentcentered learning activities using a scientific approach through problembased learning models, project-based learning and discovery learning models. One solution that can be done by history teachers in answering the challenges of the 2013 curriculum is to design learning activities through historical comics. Historical teachers can apply problem-based learning models by utilizing historical comics that are already available on the market as well as on the internet. In addition, history teachers can also apply project-based learning models through activities of making comic history by learners in accordance with the historical learning material learned. The design of learning activities through comics is expected to create innovations in the form of historical comics as a result of the design and creativity of the students. The process of learning history through the making of comics is certainly based on a scientific approach and student-centered. History teachers are asked to direct, provide solutions and suggestions to improve the quality of learning activities and learning outcomes as well as the quality of historical comic produced by students.